2015
DOI: 10.1017/s1368980015002074
|View full text |Cite
|
Sign up to set email alerts
|

Impaired quality of life in treatment-seeking obese children of Dutch, Moroccan, Turkish and Surinamese descent

Abstract: Objective: To determine the health-related quality of life (HRQOL) of overweight and obese multi-ethnic children compared with normal-weight children; and to investigate differences in HRQOL between self-and parent-proxy reports and ethnic groups. Design: Prospective cross-sectional study. Setting: Out-patient clinic where children and their parents filled out a validated HRQOL questionnaire (KIDSCREEN-52) and height, weight, waist circumference and fat percentage were measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
(70 reference statements)
0
5
0
3
Order By: Relevance
“…В литературе нами не обнаружено российских исследований, которые изучали влияние расово-ýтнической принадлежности на СÇКЖ у детей и подростков с разным статусом веса. Опубликованные результаты зарубежных исследований противоречивы, но в большинстве из них показано, что СÇКЖ у детей с ожирением снижено во всех расово-ýтнических группах [21][22][23]25].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…В литературе нами не обнаружено российских исследований, которые изучали влияние расово-ýтнической принадлежности на СÇКЖ у детей и подростков с разным статусом веса. Опубликованные результаты зарубежных исследований противоречивы, но в большинстве из них показано, что СÇКЖ у детей с ожирением снижено во всех расово-ýтнических группах [21][22][23]25].…”
Section: Discussionunclassified
“…Интересные результаты получили в своем исследовании N.N. Radhakishun и соавт., изучавшие ассоциации ожирения и СÇКЖ в пяти расово-ýтнических группах Голландии [23]. Ими не обнаружено существенных различий СÇКЖ между детьми с ожирением турецкого, марокканского, суринамского и африканского происхождения и детьми европеоидами.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Although the association between HRQOL and weight class has not yet been properly studied in a large clinical sample of children in the Netherlands, research indicates that this association is likely to be similar to that in other countries [ 23 29 ]. However, most of these studies investigated generic HRQOL and not weight-specific HRQOL, and reported only summary measures, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Although the association between HRQOL and weight class has not been yet properly studied in a large clinical sample of children in the Netherlands, research indicates that this association is likely to be similar to that in other countries [19][20][21][22][23][24][25]. However, most of these studies investigated generic HRQOL and not weight-speci c HRQOL, and reported only summary measures, i.e.…”
Section: Introductionmentioning
confidence: 99%